HALAL TOURISM OPPORTUNITIES TO INCREASE TOURIST VISITS IN INDONESIA - Akbar, Mochamad Fajar (Journal of Indonesian Tourism and Policy Studies, 2021)
The development of halal tourism in Indonesia is carried out in a sustainable manner, aiming to realize the improvement of the personality and abilities of the Indonesian people, by utilizing science and technology and taking into account the challenges of global development. Halal tourism development is developed with an approach to economic growth and equity for the people's welfare and regional development-oriented development. This study uses a qualitative method by using books and other literatures such as journals, online news, and others as the main object. The increase in Muslim tourists from year to year is an opportunity and a challenge for the tourism sector to develop halal tourism. Many countries (both Muslim and non-Muslim majority) are trying to develop halal tourism. Based on the existing concepts and principles of halal tourism, these countries generally only try to create a Muslim-friendly atmosphere. The development of halal tourism needs to be done, one of which is by conducting various researches or studies.